Commercial higher education strategies for recruiting international students in China: a catalyst or obstacle for sustainable education and learning? - Zhou, Lei; Alam, Gazi Mahabubul (Springer Nature, 2024)
In this modern era of commercialized higher education, learning and qualifications have become the essential commodities that drive nations’ economic progress. Free market principles related to consumerism appear to dictate and shape the operational framework of higher education. While a market-driven strategy may yield benefits in promoting the internationalization of higher education, it could potentially come at the expense of sustainable development of universities and proper learning. Employing a qualitative method, this study explores whether the commercialized nature and marketing of internationalized higher education contributes to or hinders its viability. It does this by comparing the practices between a Double First-Class university and a non-Double First-Class university. Findings underscore the need for more attention to be paid to creating a sustainable higher education system. Colleges and universities should strategically rebrand themselves by innovating their management and teaching systems to foster more competent international human resources, leading to sustainable universities and better prepared international students. © The Author(s) 2024.